1998
DOI: 10.1002/(sici)1097-4628(19980207)67:6<1025::aid-app9>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

The adhesion promotion mechanism of organofunctional silanes

Abstract: ABSTRACT:The adhesion promotion mechanism of organofunctional silanes has historically been attributed to the formation of an ''interpenetrating polymer network'' between a polymerized silane film and the polymer. This notion was investigated by formulating and testing two hypotheses. First, if the adhesion promotion is due to the formation of an interpenetrating polymer network, variation in the time-temperature profile of the bonding conditions should alter the extent of interdiffusion and thus interfacial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…The research reported here deals with the improvement of the mechanical characteristics of aged papers with simultaneous deacidification. It has been observed that the introduction of aminoalkylalkoxysilanes (AAAS) in a cellulose fibre web gives new desirable properties to aged or unaged papers 1–4. The experimental procedure used solutions of AAAS in ethanol, and the new properties were thought to arise from the formation of a self‐developing polysiloxane network on the fibre surfaces within the paper.…”
Section: Introductionmentioning
confidence: 99%
“…The research reported here deals with the improvement of the mechanical characteristics of aged papers with simultaneous deacidification. It has been observed that the introduction of aminoalkylalkoxysilanes (AAAS) in a cellulose fibre web gives new desirable properties to aged or unaged papers 1–4. The experimental procedure used solutions of AAAS in ethanol, and the new properties were thought to arise from the formation of a self‐developing polysiloxane network on the fibre surfaces within the paper.…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of research dealing with the improvement of the mechanical characteristics of aged papers with simultaneous deacidification, it was observed that the introduction of aminoalkylalkoxysilanes (AAAS) in a cellulose fibre web gave new desirable properties to aged or unaged papers 1–4. This technique used solutions of these compounds in ethanol, and the new properties were thought to arise from the formation of a polysiloxane network self‐developed in the paper on the fibre surface.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenology was introduced a few years ago, 19,20 but recent studies aim at characterizing in detail such a phase. 21,22 As mentioned by Drzal, 23 composite properties depend strongly on interfacial properties and interphase nature.…”
Section: Dielectric Investigation Imentioning
confidence: 94%